2005
DOI: 10.1007/s00268-004-7612-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ketoprofen in Postoperative Pain Treatment after Major Abdominal Surgery

Abstract: In recent years considerable attention has been paid to the treatment of postoperative pain, with regard to the favorable effect of adequate analgesia on patient outcome. Multimodal analgesia (e.g., opioids and nonsteroidal anti-inflammatory drugs [NSAIDs] or local anesthetics) is recommended for effective postoperative pain relief. There are few data on the use of NSAIDs in postoperative pain treatment after abdominal surgery. We conducted a randomized, double-blind, placebo-controlled study to assess the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 17 publications
0
42
0
3
Order By: Relevance
“…This is also true for metamizole, as it has been proven that co-administration of metamizole with morphine (López-Muñ oz et al 2008, Domtnguez-Ramtrez et al 2010, paracetamol or ketoprofen (Oberhofer et al 2005) is able to produce potentiation of antinociceptive effects. Domínguez-Ramírez et al (2010) demonstrated that co-administration of morphine and metamizole under acute treatment produced a significantly higher antinociceptive effect than that obtained with morphine alone.…”
Section: Interactions With Other Analgesicsmentioning
confidence: 91%
See 1 more Smart Citation
“…This is also true for metamizole, as it has been proven that co-administration of metamizole with morphine (López-Muñ oz et al 2008, Domtnguez-Ramtrez et al 2010, paracetamol or ketoprofen (Oberhofer et al 2005) is able to produce potentiation of antinociceptive effects. Domínguez-Ramírez et al (2010) demonstrated that co-administration of morphine and metamizole under acute treatment produced a significantly higher antinociceptive effect than that obtained with morphine alone.…”
Section: Interactions With Other Analgesicsmentioning
confidence: 91%
“…Over recent years, they have gained popularity as a medication to relieve postoperative pain; used alone to stop mild to moderate pains, but even more importantly as a component of multimodal analgesia (Schug and Manopas 2007). Very good effects have been attained in treatment of acute pain using metamizole in combination with NSAIDs, including ketoprofen (Oberhofer et al 2005) or with opioid analgesics (López-Muñ oz et al 2008, Baumgartner et al 2009). The efficacy of metamizole in post-operative pain therapy has been confirmed in studies conducted on humans (Edwards et al 2001, Chaparro et al 2012) and on animals (Imagawa et al 2011).…”
Section: Clinical Applications In Peoplementioning
confidence: 99%
“…Rationale: Two single-center RCTs, one including 120 postcardiac surgery ICU patients in four parallel groups (adjunctive 75 mg diclofenac, 100 mg ketoprofen, 100 mg indomethacin, or placebo) (102) and one including 43 postabdominal surgery ICU patients in two parallel groups (adjunctive 100 mg ketoprofen or placebo) (103), evaluated the role of COX-1-selective NSAIDs for postoperative ICU pain control. Pooled analysis demonstrated that NSAIDs nonsignificantly reduced pain intensity at rest at 24 hours as measured by the 0-10 VAS or NRS (MD, -0.35 cm; 95% CI, -0.91 to +0.21; low quality).…”
Section: Nsaidsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] NSAIDs and opioid analgesics have a synergic effect, 22 thereby achieving better pain control and an opioid-sparing effect with fewer adverse events in those settings. Therefore, the use of NSAIDs also could be a good strategy for the treatment of VOC in patients with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…We chose ketoprofen because its efficacy has been proven in many other pain settings. 14,15,17,[19][20][21][51][52][53][54] Since its marketing in 1973 in Europe, ketoprofen, which belongs to the propionic acid class of NSAIDs, has been widely used in France and Europe. It is, like most NSAIDs (eg, ketorolac), a nonselective cyclooxygenase inhibitor.…”
mentioning
confidence: 99%